2020
DOI: 10.1101/2020.10.27.358077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resilience in a Natural Model of Metabolic Dysfunction Through Changes in Longevity and Ageing-Related Metabolites

Abstract: The Mexican tetra, Astyanax mexicanus, has undergone remarkable physiological and behavioral changes in order to colonize a number of subterranean caves in the Sierra de El Abra region of Mexico. A hallmark of cave-adapted populations is enhanced survival under low-nutrient conditions coupled with hyperglycemia, increased body fat, and insulin resistance, but cavefish appear to avoid the progression of the respective pathologies associated with these conditions and do not exhibit reduced longevity. The metabol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 96 publications
4
10
0
Order By: Relevance
“…For instance, genes under the 'lipid catabolic process' such as lipase eb (lipeb), carnitine palmitoyltransferase 1a (cpt1aa), phospholipase D1 (pld1b) are all upregulated in SFL as compared to CFL. These results reflect the biology of these fishes in vivo, as it has been shown that surface fish undergo higher lipid breakdown while cavefish synthesize more lipid and surface fish have an increased innate immune response compared to cavefish (5,7,14).…”
Section: Cell Line Activitysupporting
confidence: 65%
“…For instance, genes under the 'lipid catabolic process' such as lipase eb (lipeb), carnitine palmitoyltransferase 1a (cpt1aa), phospholipase D1 (pld1b) are all upregulated in SFL as compared to CFL. These results reflect the biology of these fishes in vivo, as it has been shown that surface fish undergo higher lipid breakdown while cavefish synthesize more lipid and surface fish have an increased innate immune response compared to cavefish (5,7,14).…”
Section: Cell Line Activitysupporting
confidence: 65%
“…In addition to Pparγ, we investigated whether its activators (ligands) are also more abundant in the liver of Pachón cavefish compared to surface fish. Using published lipidomic profiling data (Medley et al, 2020), we found three natural activators (linolenic (C18:3), linoleic (C18:2), and arachidonic acids (C20:4)), to be more abundant in the livers of Pachón cavefish compared to surface fish livers (Fig. 4A).…”
Section: The Regulation Of Pparγmentioning
confidence: 97%
“…2E). Using available lipidomics data (Medley et al, 2020), we compared the abundance of MUFAs in cavefish. We found that both oleic acid and palmitoleic acid were present in higher levels in refed Pachón cavefish livers compared to surface fish samples and cavefish samples starved for 30 days (Fig.…”
Section: Cavefish Increase Lipogenesis In the Livermentioning
confidence: 99%
See 2 more Smart Citations